Promoting a research agenda for cancer treatment for intravenous devices with clinicians in Europe; the PRACTICE survey - Duggan, Caitriona; Hernon, Orlaith; Simpkin, Andrew J; Manasek, Viktor; de la Torre-Montero, Julio C; Santos-Costa, Paulo; Moss, Jonathan G; Ruhlmann, Christina H; Taxbro, Knut; Rodriguez-Calero, Miguel Angel; Oom, Rodrigo; Barroca, Rita; et al. (My University, 2025)
The PRACTICE survey aimed to characterize vascular access device (VAD) practices for systemic anti-cancer therapy (SACT) across Europe, addressing gaps in clinician decision-making, training, and complication management.
Keywords: Antineoplastic Agents; Professional Practice; Vascular Access Devices